2003
DOI: 10.1046/j.1365-313x.2003.01947.x
|View full text |Cite
|
Sign up to set email alerts
|

The plasma membrane aquaporin NtAQP1 is a key component of the leaf unfolding mechanism in tobacco

Abstract: SummaryEpinastic leaf movement of tobacco is based on differential growth of the upper and lower leaf surface and is distinct from the motor organ-driven mechanism of nyctinastic leaf movement of, for example, mimosa species. The epinastic leaf movement of tobacco is observed not only under diurnal light regimes but also in continuous light, indicating a control by light and the circadian clock. As the transport of water across membranes by aquaporins is an important component of rapid plant cell elongation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 37 publications
(39 reference statements)
2
60
0
3
Order By: Relevance
“…Peeters, unpublished data), and it remains possible that one of the expansins that we have not examined in this study is important in the differential regulation of hyponastic growth. Additionally, other cell wall-loosening enzymes (for review, see Cosgrove, 1997), aquaporins (Siefritz et al, 2004), or K 1 -channels (Fuchs et al, 2003) could be differentially expressed, resulting in submergence-induced hyponastic growth of R. palustris petioles.…”
Section: Rpexpa1 Is Probably Not the Downstream Target For Regulationmentioning
confidence: 99%
“…Peeters, unpublished data), and it remains possible that one of the expansins that we have not examined in this study is important in the differential regulation of hyponastic growth. Additionally, other cell wall-loosening enzymes (for review, see Cosgrove, 1997), aquaporins (Siefritz et al, 2004), or K 1 -channels (Fuchs et al, 2003) could be differentially expressed, resulting in submergence-induced hyponastic growth of R. palustris petioles.…”
Section: Rpexpa1 Is Probably Not the Downstream Target For Regulationmentioning
confidence: 99%
“…Moreover, many plant organs, such as leaves, cotyledons, or stems, perform extensive rhythmic growth movements, which very likely involve also considerable volume changes in nonspecialized cells (e.g. Jarillo et al, 2001;Siefritz et al, 2004), occurring within tens of minutes to hours. Cells in fast-growing plant tips-in elongation zones, including pollen tubes-are likely to fall in the same category.…”
Section: Physiological Relevancementioning
confidence: 99%
“…Physiological and genetic studies have confirmed the direct role of AQPs in improving plant water relation under salt stress (Martre et al, 2002;Siefritz et al, 2002;Siefritz et al, 2004). Sequence homology patterns have led to the classification of AQPs in most plant species into 4 subgroups: plasma membrane intrinsic proteins (PIPs), tonoplast intrinsic proteins (TIPs), nodulin-26-like intrinsic membrane proteins (NIPs), and small basic intrinsic proteins (SIPs) (Maurel et al, 2008).…”
Section: Introductionmentioning
confidence: 99%